A qualitative study of international students' sexual health information behaviours: The case of Chinese men who have sex with men. Issue 1 (28th December 2022) - Chang, Shanton; Kuang, Peng; Trumpour, Sabrina
There has been an increase in HIV diagnoses among Chinese men who have sex with men international students (CMISs) in Australia. However, there is not a lot of understanding about the sexual health information of this cohort of transient students. There are often assumptions of low sexual health literacy and other vulnerabilities made about this cohort, but the actual cultural and systemic barriers are not well understood. In particular, there is a lack of understanding about their sexual health information behaviours. Data were collected through semi-structured in-depth interviews among ten CMISs in Australia, recruited from social dating apps and snowballing methods. Within this sample, there was a diversity in CMISs' prior sexual health knowledge, sources of sexual health information and engagement with the Australian LGBTIQA+ community. A key concern amongst those interviewed was a lack of in-depth knowledge about the Australian health system. This article challenges some of the assumptions about CMISs' sexual health information behaviours and calls for a more nuanced approach when engaging with them. In order to provide relevant and timely sexual health information to CMISs, these results point to four areas for attention and improvement. These are use of peer mentoring, messaging disseminated through Chinese social media, activating a more inclusive LGBTIQA+ community and increasing awareness about the Australian health system.